Application of carbon allotropes composites for targeted cancer therapy drugs: A review - Niazvand, Firooze; Wagh, Pushkaraj Rajendra; Khazraei, Elham; Borzouyan Dastjerdi, Mahsa; Patil, Chanakya; Najar, Ishtiyaq Ahmad (Journal of Composites and Compounds, 2021)
In recent years, various drug carrier nanomaterials have been investigated to improve drug delivery systems in cancer treatment. However, an ongoing requirement exists for more beneficial therapeutic materials, yielding rapid clearance, high capacity for reducing systemic toxicity via specific-tumor targeting, and superior drug solubility. Given that, carbon allotropes, including Active Carbon (AC), carbon nanotubes (CNTs), graphene and graphene oxides (GOs), nanodiamonds (NDs), fullerenes, carbon nanohorns, soporous carbons, and carbon dots, have been studied owing to their high thermal conductivity, rigid structure, flexibility for modification and functionalization, adequate surface-to-volume ratio, and high biocompatibility. This review aims to overview recent advances in applying different carbon allotrope composites in drug delivery-based cancer therapy systems.